Strategi Komunikasi dan Pemasaran Digital dalam Pelestarian Batik Sukapura - Santi Susanti; Muhammad Rifki Adinur Zein (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Sukapura batik represents the local wisdom of the Tasikmalaya Regency community, showcasing their relationship with the surrounding natural and social environments. This batik has distinct characteristics, particularly in its color palette, which features dark blue, maroon, and beige tones. Despite its long history, Sukapura batik struggles to achieve the same recognition as well-known batik from regions like Cirebon, Solo, and Pekalongan. As a result, the number of batik artisans in Sukaraja has gradually declined. This research examines the communication efforts to preserve Sukapura batik and explore its growth potential. Using a qualitative method and a case study approach, the study gathers data from participants through interviews, observations, and the analysis of written documents, both online and offline. The results showed that there are differences in marketing strategies between craftsmen in Sukapura Village and Janggala Village. Sukapura Village craftsmen still rely on traditional marketing, while the Gandok Jaya Mukti Joint Business Group (KUB) utilizes exhibitions and social media. The main challenges are low digital literacy and limited capital. Sukapura batik has the potential for development, despite challenges posed by global competition. Realizing this potential depends on support from the local government in areas such as human resource development, as well as marketing and promotion through online channels. The sustainability of Sukapura batik relies on the government's and policymakers' proactive involvement to devise and implement strategies that enhance promotional and marketing endeavors, particularly those targeting the younger generation. Efforts to raise awareness of Sukapura batik require collaboration between artisans, the government, and the community. One approach is through education and training for young batik makers, as well as providing facilities to support digital marketing.